2011
DOI: 10.1016/j.phrp.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Predictive Model for Type 2 Diabetes Mellitus Using Genetic and Clinical Data

Abstract: ObjectivesRecent genetic association studies have provided convincing evidence that several novel loci and single nucleotide polymorphisms (SNPs) are associated with the risk of developing type 2 diabetes mellitus (T2DM). The aims of this study were: 1) to develop a predictive model of T2DM using genetic and clinical data; and 2) to compare misclassification rates of different models.MethodsWe selected 212 individuals with newly diagnosed T2DM and 472 controls aged in their 60s from the Korean Genome and Epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A prototypical approach can be found in [28], where a cohort is divided into subgroups based on glycemic control status and regression analysis is used to identify significant independent predictors. More generally, algorithmic approaches have been applied to various other aspects of diabetes and diabetes care, including the diagnosis of diabetes [29–32], prediction of complications [3337], genetic background and environment [3841], and large scale factors such as healthcare spending on diabetes and diabetes-related subjects, managing health care systems, and enterprise-scale identification of patients with type 2 diabetes [4246]. An extensive and well written review of the efforts mentioned above as well as many others can be found in [47].…”
Section: Discussionmentioning
confidence: 99%
“…A prototypical approach can be found in [28], where a cohort is divided into subgroups based on glycemic control status and regression analysis is used to identify significant independent predictors. More generally, algorithmic approaches have been applied to various other aspects of diabetes and diabetes care, including the diagnosis of diabetes [29–32], prediction of complications [3337], genetic background and environment [3841], and large scale factors such as healthcare spending on diabetes and diabetes-related subjects, managing health care systems, and enterprise-scale identification of patients with type 2 diabetes [4246]. An extensive and well written review of the efforts mentioned above as well as many others can be found in [47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Lee et al used various classification algorithms, such as SVM and logistic regression, to predict T2D by employing 499 known SNPs from 87 T2D-related genes [133]. Finally, in [134], authors used support vector machines to predict tyrosine kinase ligand-receptor pairs from their amino acid sequences.…”
Section: Dm Through Machine Learning and Data Miningmentioning
confidence: 99%
“…As per the survey of above papers we can find many gaps that are to be filled, which are usage of larger dataset [23,34], outlier detection [35], improving prediction model [34], integration of optimization techniques to hybrid prediction model [33], implementation of prediction models for other diseases on android mobile [31], development of prediction model that include type 1 treatment plans with more attributes [30], usage of datasets of multiple classes [4].…”
Section: Discussionmentioning
confidence: 99%
“…A multi stage adjustment model with low misclassification rate which predicts which persons are most likely to develop diabetes is built by using KoGES dataset [23]. A physiological model which can predict the blood glucose level 30 min in advance was developed using five patients data by training SVR with physiological features.…”
Section: Different Prediction Models Used For Diabetesmentioning
confidence: 99%